Information Accessibility for Persons with Disabilities in Lithuania: Regulation, Monitoring and Economic Aspects - Gulbinė, Lina (PRAWO i WIĘŹ, 2023)
The author analyses information accessibility for persons with disabilities in three scopes: Lithuanian legislation on information accessibility, the main criteria for monitoring information accessibility in Lithuania, and the economic value of information accessibility for Lithuanian citizens with reduced mobility and business.